Rabbit Skeleton Preparation in Boiling Method - Hamid, Asadullah (Journal of Natural Sciences – Kabul University, 2024)
Rabbit is a domestic animal that has important role in research, economy and different social aspects. Rabbit’s meat can be used as a daily nutrient. The skeleton of the rabbit is very simple and precise compare to other domestic mammals and has less anatomical differences. The purpose of this research work is to prepare a rabbit skeleton by boiling method and find morphological and anatomical differences of its skeleton. In this work a rabbit is slaughtered by Islamic way and prepared its skeleton by boiling technique. The results of this research shows that the skeleton of the rabbit has some species specific variation in compare to other domestic mammals.